Higher education capitalism in Indonesia as a social problem: A case study in the digital age - Doddy Sumbodo Singgih; Bagong Suyanto; Septi Ariadi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
Since the Indonesian state entered the reform era in 1998, several state universities that were centers of scientific development had their legal status changed by the government to become State-Owned Legal Entity University. From a sociological perspective, changes in legal status are commonly understood as institutional changes, which include changes in the norms that refer to governance, changes in governance procedures, and changes in organizational structure and governance. Some of the State Universities that have changed their legal status (institutions) are the Universitas Indonesia (UI), Universitas Gadjah Mada (UGM), Institut Pertanian Bogor (IPB), Institut Teknologi Bandung (ITB), Universitas Sumatera Utara (USU), Universitas Pendididikan Indonesia (UPI), and Universitas Airlangga (UNAIR). This article will describe whether, in today’s digital era, these changes cause social problems of their own, especially social problems related to inter-structural relationships in academic activities on campus. This study employed Mixed Methods Research and 100 students as a sample of this study. The results found the fact that most of the student respondents (55.42%) considered that social problems that arise in State-Owned Legal Entity University were related to the capitalism of higher education. This research also found the impact of institutional changes being State-Owned Legal Entity University is a change in the inter-structural relationship among the academic community in carrying out academic activities to become exploitative, hegemonic, and repressive. Therefore these changes in an inter-structural relationship were also considered as a social problem.